2015
DOI: 10.1038/srep13750
|View full text |Cite|
|
Sign up to set email alerts
|

Whole genome and transcriptome sequencing of matched primary and peritoneal metastatic gastric carcinoma

Abstract: Gastric cancer is one of the most aggressive cancers and is the second leading cause of cancer death worldwide. Approximately 40% of global gastric cancer cases occur in China, with peritoneal metastasis being the prevalent form of recurrence and metastasis in advanced disease. Currently, there are limited clinical approaches for predicting and treatment of peritoneal metastasis, resulting in a 6-month average survival time. By comprehensive genome analysis will uncover the pathogenesis of peritoneal metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 28 publications
(28 reference statements)
2
71
0
Order By: Relevance
“…Only one study mentioned that IQUB expression was increased in gastric cancer by transcriptome sequencing 5. In our study, we noticed that the expression of IQUB in breast cancer tissues was not only significantly increased, but also positively correlated with the pathological differentiation of breast cancer, suggesting that IQUB may have a bearing on the malignant progression and prognosis of breast cancer.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Only one study mentioned that IQUB expression was increased in gastric cancer by transcriptome sequencing 5. In our study, we noticed that the expression of IQUB in breast cancer tissues was not only significantly increased, but also positively correlated with the pathological differentiation of breast cancer, suggesting that IQUB may have a bearing on the malignant progression and prognosis of breast cancer.…”
Section: Discussionsupporting
confidence: 52%
“…However, there were few studies exploring the role of IQUB in human diseases. Only one tumor‐related study referred to IQUB which found that IQUB was upregulated in gastric cancer tissues by transcriptome sequencing,5 but the mechanism was not clear. Combined with our transcriptome sequencing in breast cancer, we speculated that IQUB may act an important role in the development of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Catumaxomab, an anti-EpCAM monoclonal antibody, coupled with intraperitoneally administered paclitaxel are recommended to effectively relieve gastric cancer-derived peritoneal metastasis [25]. Zhang et al recently identified 27 somatic mutated genes and infusion of GPX4 and MPND in the19q13.3-13.4 region by whole-genome and -transcriptome sequencing of one patient [4]. The different mutation events in the present study may be attributable to the different pathological characteristics of the selected specimen.…”
Section: Discussionmentioning
confidence: 83%
“…Although a steady decline in cancer incidence and mortality have been observed in recent years, an estimated 951,600 new gastric cancer cases and 723,100 deaths were reported in 2012. Approximately 40% of gastric cancer cases occur in China, and many are diagnosed at an advanced stage with a tendency toward metastasis and recurrence [4]. Peritoneal carcinoma occurs in both the advanced and early stages of gastric cancer and is the most common type of metastasis and recurrence [57].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the risk factors for developing metachronous peritoneal carcinomatosis are advanced stage at diagnosis, right-side cancer location, infiltrative or ulcero-infiltrative carcinomas, and history of perforation and obstruction in colorectal cancer (4)(5)(6)(7), but these factors are not reliable predictors for peritoneal metastasis in individuals. Although many researchers have investigated the mechanism of peritoneal dissemination in terms of genetic variations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), common changes of gene expression in tumor progression to peritoneal metastasis have not yet been clarified.…”
mentioning
confidence: 99%